Building a dictionary of Malay language part-of-speech tagged words using Bahasa WordNet and Bahasa Indonesia resources / Mohamed Lubani and Rohana Mahmud - Lubani, Mohamed; Mahmud, Rohana (2015)
Assigning grammatical categories to words in natural text is a vital step in processing natural language. Language resources and text processing tools such as part-of-speech (POS) can be used to assign each word the corresponding grammatical category based on its context. Such resources are available for the major languages such as English, Spanish and Japanese. However, the lack of resources for Malay language makes it very hard to develop new processing tools and contribute to the automation of the language processing. In this paper, a Malay POS dictionary is built using Bahasa wordnet and a POS tagged of Indonesian corpus, as well as a monolingual Malay dictionary. The output is a list of 25,778 Malay POS tagged words where each word is assigned all its possible grammatical categories. The proposed process can also be used as a guideline for future improvements